Mechanisms for implementing modern public management in Algerian Public Health Institutions - Hanane, Kada; Naziha, Hocine (The International tax journal, 2026)
This article examines the mechanisms for implementing modern public management in Algerian public health institutions in light of the reforms introduced by the new Health Law. It focuses on the adoption of program and performance budgeting to improve the efficiency of resource utilization, the institutional project as a tool for strategic planning, as well as performance and objective-based contracts that link institutional financing to measurable results. The article concludes that these mechanisms constitute a step toward the modernization of health management; however, they require the strengthening of capacities and the development of monitoring and evaluation systems.